2008
DOI: 10.1007/s10712-008-9041-3
|View full text |Cite
|
Sign up to set email alerts
|

GPS Height and Gravity Variations Due to Ocean Tidal Loading Around Taiwan

Abstract: This study presents predicts ocean tidal loading (OTL) effects using a Green's function approach and validates a novel tidal model for Taiwan. Numerical integration of OTL is performed using the Gauss quadrature method and a local tidal model for the inner zone and a global model for the outer zone. Observed time series of GPS-derived vertical displacements and gravity variations (3-7 days) at five co-located GPS-gravimeter stations along the South East China and Taiwan coasts were utilized to assess the accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Meanwhile, an average rate close to 6.17 × 10 −6 m/s derived from the associated oscillation of the Earth's surface also shows an agreement with the seismic data. Note that the frequency of the amplification is different compared with the well-known frequency-dependent effects (such as the lunar elliptic tides, lunar semi-diurnal tides, lunar-solar semi-diurnal tides and so on) on the surface displacements [25,26].…”
Section: Introductionmentioning
confidence: 98%
“…Meanwhile, an average rate close to 6.17 × 10 −6 m/s derived from the associated oscillation of the Earth's surface also shows an agreement with the seismic data. Note that the frequency of the amplification is different compared with the well-known frequency-dependent effects (such as the lunar elliptic tides, lunar semi-diurnal tides, lunar-solar semi-diurnal tides and so on) on the surface displacements [25,26].…”
Section: Introductionmentioning
confidence: 98%
“…This was shown in a study of OTL corrections for superconducting gravity (SG) measurements at the Hsinchu station by Hwang et al (2009), who found that some of the global OTL programs produce anomalously large values that cannot be used for gravity corrections. The Hsinchu SG station is about 8.6 km to the Taiwan Strait and situated at an elevation of 78 m. Earlier studies suggest that gravity effects and displacements due to OTL can be very large at offshore islands with large tidal amplitudes (Lambert et al 1998;Yamamoto et al 2001;Huang et al 2008;Yeh et al 2008;Hwang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Regarding short-term variations, offsets in GPS coordinate time-series data before and after earthquakes are frequently presented to illustrate co-seismic dislocations [2,[13][14][15]. In addition, GPS signals also carry obvious annual and semiannual cycles along with tropospheric delay, ionospheric refraction, and ocean tidal loading [16][17][18][19]. These aforementioned effects need to first be removed from and/or mitigated in GPS data in order to effectively retrieve surface displacements in earthquake preparation periods.…”
Section: Introductionmentioning
confidence: 99%